An Evaluation of a Leadership Portfolio Project for Principals. - Dixon, Kathryn; Dixon, R.C. (2003)
Early in 2002, the Swan Education District of Western Australian initiated a professional portfolio project for educational leaders. The portfolio was designed for principals to demonstrate leadership competency as underpinned by the Education Department of WA draft competency framework. This study is an evaluation of the project. The focus of the evaluation is on issues related to participant principals' perceptions of their experiences in creating the portfolio. It sought to clarify the adequacy of the training and preparation phase, whether or not the goals set were achieved, perceptions of the value of creating a portfolio and perceptions of any effects that resulted as a direct consequence of developing their portfolio.